If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8v + 28 = -3(v + -2) Reorder the terms: 28 + 8v = -3(v + -2) Reorder the terms: 28 + 8v = -3(-2 + v) 28 + 8v = (-2 * -3 + v * -3) 28 + 8v = (6 + -3v) Solving 28 + 8v = 6 + -3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '3v' to each side of the equation. 28 + 8v + 3v = 6 + -3v + 3v Combine like terms: 8v + 3v = 11v 28 + 11v = 6 + -3v + 3v Combine like terms: -3v + 3v = 0 28 + 11v = 6 + 0 28 + 11v = 6 Add '-28' to each side of the equation. 28 + -28 + 11v = 6 + -28 Combine like terms: 28 + -28 = 0 0 + 11v = 6 + -28 11v = 6 + -28 Combine like terms: 6 + -28 = -22 11v = -22 Divide each side by '11'. v = -2 Simplifying v = -2
| 19-c=4 | | -7(k+3)-(-8k+7)=5 | | 2+3x-5x=-4 | | 16(x-9)=4(2a-x) | | -6(u+6)=4u+4 | | 1/4t+3/5=2/5-t | | -7x+3-5x=-57 | | 8+28m-24-12m=0 | | -34=5x+3(x+2) | | f(x)=a(x+3)(x+1)(x-4) | | 5y-7x=12 | | 6x^2+3xy+3y^2=108 | | x=-1.5+0.5y | | -3t^2+16t-11=0 | | 16x^2+64t+64=0 | | 6-2x(3-12)=2x+90 | | 20x+5=-2x | | 3(u-5)-6u=-33 | | 0.4-8.1y-2.7y=1-10.8y-0.6 | | 11(k-2)+[k-3(k+1)]=0 | | (3c-8)(3c-8)=0 | | y=-3+2y | | 7(y+2)-5y=-4 | | 8-28m-24-12m=0 | | 2(t-1)+3t=2 | | -2(d+6)=-20 | | 2*j=25+j | | K-(-40)=32 | | 2t-4=2 | | 36=4(8x+1) | | 3(w+7)=-3 | | 8(1-4x)+8(x+3)=32 |